2021
DOI: 10.1016/j.ajhg.2021.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Functional annotation of the 2q35 breast cancer risk locus implicates a structural variant in influencing activity of a long-range enhancer element

Abstract: A combination of genetic and functional approaches has identified three independent breast cancer risk loci at 2q35. A recent fine-scale mapping analysis to refine these associations resulted in 1 (signal 1), 5 (signal 2), and 42 (signal 3) credible causal variants at these loci. We used publicly available in silico DNase I and ChIP-seq data with in vitro reporter gene and CRISPR assays to annotate signals 2 and 3. We identified putative regulatory elements that enhanced cell-type-specific transcription from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…Besides proximal promoter elements, sequences far upstream (telomeric) and downstream (centromeric) of the transcriptional start site (TSS) regulate IGFBP5 transcription ( Figure 5 ). The far upstream regulatory elements are located in the 2q35 protein-coding gene desert ( 23 27 ). This region has been recognized as a BC susceptibility locus, where several single nucleotide polymorphism (SNP) sites and a deletion variant (called enCNV or esv3594306) have been identified, potentially linking IGFBP5 to BC risk ( 25 27 , 129 ).…”
Section: Regulation Of Igfbp5 Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides proximal promoter elements, sequences far upstream (telomeric) and downstream (centromeric) of the transcriptional start site (TSS) regulate IGFBP5 transcription ( Figure 5 ). The far upstream regulatory elements are located in the 2q35 protein-coding gene desert ( 23 27 ). This region has been recognized as a BC susceptibility locus, where several single nucleotide polymorphism (SNP) sites and a deletion variant (called enCNV or esv3594306) have been identified, potentially linking IGFBP5 to BC risk ( 25 27 , 129 ).…”
Section: Regulation Of Igfbp5 Expressionmentioning
confidence: 99%
“…The far upstream regulatory elements are located in the 2q35 protein-coding gene desert ( 23 27 ). This region has been recognized as a BC susceptibility locus, where several single nucleotide polymorphism (SNP) sites and a deletion variant (called enCNV or esv3594306) have been identified, potentially linking IGFBP5 to BC risk ( 25 27 , 129 ).…”
Section: Regulation Of Igfbp5 Expressionmentioning
confidence: 99%
“…used CRISPR interference (CRISPRi) to introduce repressive histone modifications at an enhancer element (annotated by the most significant GWAS SNP at this locus) and demonstrated that this resulted in reduced levels of expression of two long noncoding RNAs ( CUPID1 and 2 ) and the presumed target gene CCND1 [ 22 ]. We have recently shown that targeting a catalytically inactive Cas9 fused to an activating VPR domain (CRISPRa) to an enhancer element at the 2q35 breast cancer risk locus increases expression of IGFBP5 (mapping ~400 kb distal) but neither of the neighbouring genes IGFBP2 and RPL37A (~460 kb and ~600 kb, respectively) [ 99 ]. A genome-wide framework for mapping gene regulation using CRISPRi has been developed; in this approach, using a high multiplicity of infection, random combinations of CRS were perturbed in the erythroleukaemia cell line K562 and expression of target genes (defined as K562-expressed genes within 1Mb of the CRS) was assayed using single-cell RNA-seq [ 100 ].…”
Section: Linking Candidate-regulatory Sequences With Putative Target ...mentioning
confidence: 99%
“…Locus-specific functional annotation studies for at least 17 loci (defined for these purposes as chromosomal regions) have been reported by BCAC investigators and collaborators at 1p11.2 [ 25 ], 2q33 [ 27 ], 2q35 [ 12 , 13 , 99 ], 4q24 [ 14 ], 5p15.33 [ 28 ], 5p12 [ 24 ], 5q11.2 [ 15 ], 6q25 [ 16 ], 8q24 [ 17 ], 9q31.2 [ 18 ], 10q21.1 [ 19 ], 10q26 [ 21 ], 11q13 [ 23 ], 12p11 [ 26 ], 12q24 [ 92 ], 17q22 [ 20 ] and 19p13 [ 29 ]. These analyses, published predominantly prior to the recent global fine-mapping analysis, begin with locus-specific fine-scale mapping to define independent signals and CCVs.…”
Section: Locus-specific Functional Annotation Studiesmentioning
confidence: 99%
See 1 more Smart Citation